sj-pdf-1-wso-10.1177_17474930211040720 - Supplemental material for Cerebrovascular disease at young age is related to mother’s health during the pregnancy—The Northern Finland Birth Cohort 1966 study - Ina Rissanen (8138454); Mirjam I Geerlings (9257008); Seppo Juvela (11421845); Jouko Miettunen (150275); Markus Paananen (1777792); Sami Tetri (3582323) (2021)
Supplemental material, sj-pdf-1-wso-10.1177_17474930211040720 for Cerebrovascular disease at young age is related to mother’s health during the pregnancy—The Northern Finland Birth Cohort 1966 study by Ina Rissanen, Mirjam I Geerlings, Seppo Juvela, Jouko Miettunen, Markus Paananen and Sami Tetri in International Journal of Stroke